Морфология личинки Wohlfahrtia intermedia Portsch., 1887 (Diptera, Sarcophagidae) - Валентюк, Е.И. (Вестник зоологии, 1973)
A description is given of Wohlfahrtia intermedia P o r t s c h. larva of all three ages,. Morphological characters are distinguished for diagnostics of each age, the drawings are presented.